Considering the nature and structure of atmospheric weathering while the occurrence of daily dry periods in west and northwest of Iran - hossein Mir Mousavi; Masoud Jalali; enayet asadolahi (تحقیقات کاربردی علوم جغرافیایی)
In this research, coding the rainfalls, prepares daily 45 stations with the statistical period of 20 years to zero and one codes to realize the daily dry periods in west and north west of the country and then, by establishing the main condition of occurrence of code one for 30 stations, we extracted the dry 4 to 10-day frequencies. And the results gained of considering the atmospheric weathering, shows that the most clear rotational pattern in sea level is related to Siberia-Europe high-pressure panels and sometimes both of them that increase the rotation on the region and also, the local high-pressure reinforcement and there is a high altitude in atmospheric middle level which is derived from sample patterns and is placed on the studied region and these sample patterns are from omega, bi-polar and rex models that they are on Russia and Scandinavian countries with some changes. The 500 level TAVA and omega shows well that in most regions, the air course, has decreasing case and so, we can result that placement of a high altitude in atmospheric middle and upper level on the high-pressures of the earth, causes the weather stability and lack of rainfall and as a result, the stability and durability of these conditions for several days, is related to sample patterns.